Analysis of information security service for internet application - Shanker, Ravi; Sahil Verma, Dr.; Kavita, Dr. (International Journal of Engineering and Technology, 2018)
Background/Objectives: With the proliferation of online platforms, information is generated every second, and there is an urgent need to firstly store the huge amount of data and secondly to secure that data. The level of sophistication is increasing day by day, so alongside the demand for excessive computational power and resources also hikes up. With the advancements in technology and with the concepts like globalization coming into picture, people find the need of sharing information important. Methods/Statistical Analysis: Information security aspects are analyzed based on confidentiality, integrity, availability, authentication, authorization and non-Repudiation. Findings: Different web application needs different security parameter and out of these authentication and access control are among the top security issues which can be resolved by using two factor and three factor authentication and are more effective with respect to mobility. Application/Improvement: Most handheld devices have built-in sensors which can be used for self authentication and authorization. Device ID, fingerprint, iris, SMS based OTPs add extra security to information security.Â Â